Designer broad-spectrum polyimidazolium antibiotics - Zhong, Wenbin (2021)
For a myriad of different reasons most antimicrobial peptides (AMPs) have failed to reach clinical application. Different AMPs have different shortcomings including but not limited to toxicity issues, potency, limited spectrum of activity, or reduced activity in situ. We synthesized several cationic peptide mimics, main-chain cationic polyimidazoliums (PIMs), and discovered that, although select PIMs show little acute mammalian cell toxicity, they are potent broad-spectrum antibiotics with activity against even pan-antibiotic-resistant gram-positive and gram-negative bacteria, and mycobacteria. We selected PIM1, a particularly potent PIM, for mechanistic studies. Our experiments indicate PIM1 binds bacterial cell membranes by hydrophobic and electrostatic interactions, enters cells, and ultimately kills bacteria. Unlike cationic AMPs, such as colistin (CST), PIM1 does not permeabilize cell membranes. We show that a membrane electric potential is required for PIM1 activity. In laboratory evolution experiments with the gram-positive Staphylococcus aureus we obtained PIM1-resistant isolates most of which had menaquinone mutations, and we found that a site-directed menaquinone mutation also conferred PIM1 resistance. In similar experiments with the gram-negative pathogen Pseudomonas aeruginosa, PIM1-resistant mutants did not emerge. Although PIM1 was efficacious as a topical agent, intraperitoneal administration of PIM1 in mice showed some toxicity. We synthesized a PIM1 derivative, PIM1D, which is less hydrophobic than PIM1. PIM1D did not show evidence of toxicity but retained antibacterial activity and showed efficacy in murine sepsis infections. Our evidence indicates the PIMs have potential as candidates for development of new drugs for treatment of pan-resistant bacterial infections.